2013
DOI: 10.1371/journal.pone.0069521
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cells Potentiate Interferon-γ Production in a Novel Tripartite Culture Model of Human Cerebral Malaria

Abstract: We have established a novel in vitro co-culture system of human brain endothelial cells (HBEC), Plasmodium falciparum parasitised red blood cells (iRBC) and peripheral blood mononuclear cells (PBMC), in order to simulate the chief pathophysiological lesion in cerebral malaria (CM). This approach has revealed a previously unsuspected pro-inflammatory role of the endothelial cell through potentiating the production of interferon (IFN)-γ by PBMC and concurrent reduction of interleukin (IL)-10. The IFN-γ increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 79 publications
2
9
1
Order By: Relevance
“…Expression of the classical co-stimulatory molecules CD80 and CD86 were undetectable on resting and activated BECs (data not shown). Comparable changes in phenotype were observed when BECs were activated using IFN-γ instead of TNFα ( Figure 1—figure supplement 1 ) Together, these results confirm and extend previous findings ( Wheway et al, 2013 ) and indicate that BECs are equipped to present antigens under inflammatory conditions. Up-regulation of MHC class II molecules via inflammation induced CIITA activity has been associated with increased susceptibility of EAE, yet how increased MHC-II expression contributes to actual disease has so far not been described ( Reith et al, 2005 ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Expression of the classical co-stimulatory molecules CD80 and CD86 were undetectable on resting and activated BECs (data not shown). Comparable changes in phenotype were observed when BECs were activated using IFN-γ instead of TNFα ( Figure 1—figure supplement 1 ) Together, these results confirm and extend previous findings ( Wheway et al, 2013 ) and indicate that BECs are equipped to present antigens under inflammatory conditions. Up-regulation of MHC class II molecules via inflammation induced CIITA activity has been associated with increased susceptibility of EAE, yet how increased MHC-II expression contributes to actual disease has so far not been described ( Reith et al, 2005 ).…”
Section: Resultssupporting
confidence: 89%
“…BECs have been shown to express MHC-I while MHC-II is virtually absent. Inflammation induced activation of BECs causes increased expression of MHC-II as well as of the co-stimulatory molecule CD40 and enhanced their ability to stimulate the proliferation of allogeneic T-cells in-vitro ( Wheway et al, 2013 ). Although BECs have been shown to take up soluble antigens by macro-pinocytosis and clathrin-coated pits ( Wheway et al, 2013 ), not much is known about their capacity to process and present internalized antigens.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, PBMCs, along with HBEC, interact with the iRBCs, leading to upregulation of the expression of inflammatory genes. 7 Very recently Moxon et al provided novel insight into the pathogenesis of CM linking loss of the endothelial protein C receptor (EPCR) on brain vessels, caused by cytoadherent iRBCs, with localized coagulation, inflammation, and disruption of endothelial barrier function. 8,9 Blood-brain barrier serves as a key interface between the central nervous system and the blood, restricting the free flow of physiological molecules between the bloodstream and parenchyma.…”
Section: Introductionmentioning
confidence: 99%
“…Our results show that CXCL10 production by PBMCs in response to P. falciparum is IFN- γ -dependent. This finding is consistent with previous studies showing that CXCL10 production in human brain endothelial cell-PBMC co-cultures is largely IFN- γ -dependent (Khaw et al ., 2013). Previous studies have identified γδ T cells, NK cells and conventional αβ T cells as sources of IFN- γ in P. falciparum -stimulated PBMCs (D'Ombrain et al ., 2007 a , 2007 b ), suggesting that IFN- γ production from these cells facilitates down-stream CXCL10 production from CD14 + monocytes in the blood.…”
Section: Discussionmentioning
confidence: 99%